Teaching Islam Through Cultural Symbol: Educational Values of Rimpu in Bima West Nusa Tenggara - Arwitasari; Marzuki, Halimatuzzahro; Hayati, Wirna (el-Tarbawi, 2023)
Covering aurat is one of Islamic teachings in which its implementation can vary according to the local cultural context. In Bima, West Nusa Tenggara, Rimpu stands as the symbols for women in adhering to Islamic law by covering their aurat properly. This present research is a qualitative study with an ethnographic approach to understand the cultural meaning of Rimpu. The findings of this study implies: (1) the educational values in Rimpu are cultural values containing moral, decency, aesthetics, and religious values as the identity and cultural symbol of the Bima community, especially for Bima women who preserve Rimpu culture as a symbol of Islamic law. By using Rimpu, Bima women adhere to the teachings of the Quran to cover their aurat properly, (2) Rimpu culture is a symbol of women's morality in performing good or bad deeds. For this reason, Rimpu culture symbolizes good morality for women. As in Islamic teachings regarding aurat, Rimpu teaches the limits of aurat, protects women when they leave their homes, preserves the honour of women from the direct gaze of non-mahram men, and control direct interaction and communication with men.